Fatigue Life Prediction of Composite Under Two Block Loading - Bendouba, M.; Aid, A.; Benguediab, M. (Engineering, Technology & Applied Science Research, 2014)
The damage evolution mechanism is one of the important focuses of fatigue behaviour investigation of composite materials and also the foundation to predict fatigue life of composite structures for engineering applications. This paper is dedicated to damage investigation of composite materials under two block loading cycle fatigue conditions. The loading sequence effect and the influence of the cycle ratio of the first stage on the cumulative fatigue life are studied. Two loading sequences, i.e., high-to-low and low-to-high cases are considered. The proposed damage indicator is connected cycle by cycle to the S-N curve and the experimental results are in agreement with model expectations. Previous experimental research is employed for validation.